The treatment of social networks for local news in Algeria: the news of the state of M’sila via Facebook as a model - khalla, marwa; sifoune, baya (Journal of Social Sciences and Humanities, 2023)
The research problem represented in the Algerian social networks’ handling of local news in the Wilayat of M’sila Via the Facebook app aimed to know the methods of this preview and to see the technological features added to the local news in the digital medium, by applying the quantitative paradigm based on the description as a type of research and the survey as a method and content analysis as a research tool, and we reached a set of results Among them: the most important news types dealt with are social, political, security, religious, cultural, and accidents, and the most prominent topics were winning the national competition for the crown of the Qur’an, advocacy , The national team in Cameroon, local reforms, as for the approved sources, we find Facebook pages, the website, satellite channels and some local sources. As for the type of attached photos, they mixed between public and personal, and the desired goals varied between news, propaganda, educational and educational, The added features include technical media, attached links, and some other digital features such as notifications and unfollowing, and therefore the news was treated The local community on Facebook is diverse, timely and directly addressing the local audience, in order to provide the academic addition to scientific research and socio-economic addition to push media practitioners in Algeria towards paying attention to local news through the digital space and informing the voice of local groups to the concerned authorities